A damage model for the simulation of crack initiation and propagation in automotive windshield laminated glass structures. Issue 4 (7th July 2021) - Fernandes, F. A. O.; de Sousa, R. J. Alves; Ptak, M.
Abstract: Accident reconstructions and numerical simulations are used to evaluate and improve protective systems. Virtual testing and numerical methods can assist in the improvement safety of vulnerable road users. This work presents the tremendous potential of using computer-aided engineering by describing the development of a windshield numerical model and its damage and fracture validation. The motivation behind this study is the possibility of using such a model in the reconstruction of road accidents involving vulnerable road users. The main goal is the development and validation of a finite element model of an automobile windshield in order to use it in further studies regarding the reconstruction of road traffic accidents. In order to validate it according to experimental studies available in the literature, the 4.8  kg standard adult headform from the European Enhanced Vehicle Safety Committee is also developed and validated. A total of eight impacts at six different locations and carried at two different impact velocities (6  m/s and 11.1  m/s) were simulated. The validation of the windshield model, and consequently the damage model employed to simulate glass cracking initiation and propagation, were accomplished by comparing the acceleration at the headform's centre of gravity and the windshield's fracture pattern against experimental data.